2020
DOI: 10.1177/0194599820904369
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in the Access and Cost of Health Care for Otolaryngologic Conditions

Abstract: Objective To demonstrate whether race, education, income, or insurance status influences where patients seek medical care and the cost of care for a broad range of otolaryngologic diseases in the United States. Study Design Retrospective cohort study using data from the Medical Expenditure Panel Survey, from 2007 to 2015. Setting Nationally representative database. Subjects and Methods Patients with 14 common otolaryngologic conditions were identified using self-reported data and International Classification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Consistent with our findings, a Medical Expenditure Panel Survey analysis (2007-2015) found, compared to non-Hispanic whites, non-Hispanic African Americans were more likely to use EDs for otolaryngologic conditions in general, and non-Hispanic African Americans and Hispanics were less likely to use otolaryngology clinic services. 34 We also previously observed that black Medicare beneficiaries with dizziness were less likely than whites to receive vestibular testing. 6 Without known medical justification, racial and ethnic differences in ED vs clinic utilization and specialty care services may result from systemic racism, barriers to establishing care, and differential care provision and trust in health care systems.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Consistent with our findings, a Medical Expenditure Panel Survey analysis (2007-2015) found, compared to non-Hispanic whites, non-Hispanic African Americans were more likely to use EDs for otolaryngologic conditions in general, and non-Hispanic African Americans and Hispanics were less likely to use otolaryngology clinic services. 34 We also previously observed that black Medicare beneficiaries with dizziness were less likely than whites to receive vestibular testing. 6 Without known medical justification, racial and ethnic differences in ED vs clinic utilization and specialty care services may result from systemic racism, barriers to establishing care, and differential care provision and trust in health care systems.…”
Section: Discussionmentioning
confidence: 82%
“…6 Without known medical justification, racial and ethnic differences in ED vs clinic utilization and specialty care services may result from systemic racism, barriers to establishing care, and differential care provision and trust in health care systems. 34,35 Investigation of the causes and consequences of observed disparities within specific communities is needed to promote equitable care provision. The observed sociodemographic patterns can inform strategies to direct patients with dizziness to the most appropriate level of care.…”
Section: Discussionmentioning
confidence: 99%
“…8 Third, primary care physicians may have difficulty in achieving successful referral to specialists for minority patients as a result of insurance issues or geographic disparities for specialists. 7 To the best of our knowledge, the present investigation is the first to examine the impact of the primary language spoken on access to a nonspecialist, in a community care setting, as it relates to self-reported sinonasal symptoms, arguing against inherent differences that might predispose one to sinonasal symptoms based on this variable alone. Unlike prior retrospective examinations of social determinants of health related to otolaryngologic symptoms, 9,10 the present study was prospectively conducted.…”
Section: Discussionmentioning
confidence: 94%
“…There may be several factors that can explain this difference. First, the lack of interpretative services for patients who are not native English speakers may result in a breakdown of communication between provider and physician regarding symptoms, diagnosis, and treatment plan 7 . Second, there may be cultural bias in play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation